2011
DOI: 10.1182/blood.v118.21.45.45
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Let-7 Processing in Adult Murine Hematopoietic Stem Cells Induces a Fetal-Like High Self-Renewal Pattern in Their Progeny

Abstract: 45 Fetal hematopoietic stem cells (HSCs) in mice differ from their adult counterparts in a number of key properties. These include a higher cycling activity, an ability to more rapidly reconstitute the HSC compartment of irradiated recipient mice, a higher output of myeloid as compared to lymphoid progeny, and a greater sensitivity to the self-renewal promoting activity of Steel factor. We have previously shown that most of these features of fetal HSCs are sustained until 3 weeks after birth at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Given that ectopic overexpression of the polycistron did not increase HSC function more than overexpression of miR-125 only, the action of miR-99 may depend on the expression of miR-125 or may be further modulated by let7 . Intriguingly, prior studies suggest that let-7 may balance the effects of miR-125 and miR-99 by suppressing HSC function ( Copley et al, 2011 , 2013 ; Zipeto et al, 2016 ), a possibility also suggested by its ability to promote differentiation of AML cells ( Pelosi et al, 2013 ). It will be important to dissect these interactions in more depth in the future, as well as post-transcriptional mechanisms that control expression of each of the miRNAs that constitute this cluster.…”
Section: Discussionmentioning
confidence: 98%
“…Given that ectopic overexpression of the polycistron did not increase HSC function more than overexpression of miR-125 only, the action of miR-99 may depend on the expression of miR-125 or may be further modulated by let7 . Intriguingly, prior studies suggest that let-7 may balance the effects of miR-125 and miR-99 by suppressing HSC function ( Copley et al, 2011 , 2013 ; Zipeto et al, 2016 ), a possibility also suggested by its ability to promote differentiation of AML cells ( Pelosi et al, 2013 ). It will be important to dissect these interactions in more depth in the future, as well as post-transcriptional mechanisms that control expression of each of the miRNAs that constitute this cluster.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence now suggest functional relationship between clustered miRNAs in which cluster members reinforce their repressive effect on their targets by acting cooperatively (Yirong Wang, Luo, Zhang, & Lu, 2016). Members of the same cluster may also perform opposing roles, an example being the case of miR‐125 and let‐7 in which let‐7c promoted differentiation of acute myeloid leukemia (AML) cells while miR‐125 facilitated the self‐renewing property of hematopoietic stem cells (HSCs) (Copley et al, 2011; Khalaj et al, 2017).…”
Section: Introductionmentioning
confidence: 99%